Career Development Program for Underrepresented in Medicine Scholars in Academic Neurology: TRANSCENDS. (20th July 2021) - Tagge, Raelle; Lackland, Daniel T.; Gorelick, Philip B.; Litvan, Irene; Cruz-Flores, Salvador; Merino, José G.; Ovbiagele, Bruce
Abstract : Background: The Training in Research for Academic Neurologists to Sustain Careers and Enhance the Numbers of Diverse Scholars (TRANSCENDS) program is a career advancement opportunity for individuals underrepresented in biomedical research funded by the National Institute of Neurologic Disorders and Stroke and American Academy of Neurology (AAN). Objective: To report on qualitative and quantitative outcomes in TRANSCENDS. Design: Early career individuals (neurology fellows and junior faculty) from groups underrepresented in medicine (UIM) were competitively selected from a national pool of applicants (2016–2019). TRANSCENDS activities comprised an online Clinical Research degree program, monthly webinars, AAN meeting activities, and mentoring. Participants were surveyed during and after completion of TRANSCENDS to evaluate program components. Outcomes: Of 23 accepted scholars (comprising 4 successive cohorts), 56% were women, 61% Hispanic/Latinx, 30% Black/African American, and 30% assistant professors. To date, 48% have graduated the TRANSCENDS program and participants have published 180 peer-reviewed articles. Mentees' feedback noted that professional skills development (i.e., manuscript and grant writing), networking opportunities, and mentoring were the most beneficial elements of the program. Stated opportunities for improvement included incorporating a mentor-the-mentor workshop, providing more transitional support for mentees in the next stage of their careers, and requiring mentees to provide quarterly reports. Conclusions: TRANSCENDS is a feasible program for supporting UIM neurologists towards careers in research and faculty academic appointments attained thus far have been sustained. Although longer-term outcomes and process enhancements are warranted, programs like this may help increase the numbers of diverse academic neurologists and further drive neurologic innovation.